2013
DOI: 10.1186/1472-6785-13-32
|View full text |Cite
|
Sign up to set email alerts
|

Methane transport and emissions from soil as affected by water table and vascular plants

Abstract: BackgroundThe important greenhouse gas (GHG) methane is produced naturally in anaerobic wetland soils. By affecting the production, oxidation and transport of methane to the atmosphere, plants have a major influence upon the quantities emitted by wetlands. Different species and functional plant groups have been shown to affect these processes differently, but our knowledge about how these effects are influenced by abiotic factors such as water regime and temperature remains limited. Here we present a mesocosm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 52 publications
1
48
0
1
Order By: Relevance
“…Plants serve as the major control of CH 4 emissions from wetlands (Bhullar et al, 2013;Joabsson and Christensen, 2001;Shannon et al, 1996). The different vegetation species effectively influence CH 4 production, oxidation and emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Plants serve as the major control of CH 4 emissions from wetlands (Bhullar et al, 2013;Joabsson and Christensen, 2001;Shannon et al, 1996). The different vegetation species effectively influence CH 4 production, oxidation and emissions.…”
Section: Introductionmentioning
confidence: 99%
“…In wetlands, reports on the importance of aerenchymatous plants for CH 4 emissions differ. Most authors have found that emissions from such vegetation are enhanced (Chanton and Dacey, 1991;Greenup et al, 2000;Koelbener et al, 2010;Noyce et al, 2014;Schimel, 1995), but reduced emissions can also occur (Bhullar et al, 2013;Fritz et al, 2011;Grünfeld and Brix, 1999). However, these studies were conducted in permanently flooded wetlands or mesocosms with a high water table.…”
Section: Discussionmentioning
confidence: 99%
“…18,19,20]. However, the muddy layer in a flooded paddy soil is continuously saturated and the impact on the CH 4 cycle of soil moisture driven by groundwater level is negligible.…”
Section: Accepted Manuscriptmentioning
confidence: 97%